Bargaining and Information: An Empirical Analysis of a Multistage Arbitration Game - Pecorino, Paul; Van Boening, Mark (Journal of Labor Economics, 2001)
We conduct an experimental analysis of final offer arbitration (FOA) with differentially informed players. Under FOA, the arbitrator must choose one of the two submitted offers. In our control, the uninformed player makes an offer to the informed player prior to the submission of offers to the arbitrator. The treatment allows negotiation after offers are submitted to the arbitrator. Because these offers are potentially binding, they may transmit privately held information and, thereby, lower the dispute rate. We find that allowing negotiation in the face of potentially binding offers lowers the dispute rate by 27 percentage points.